(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To synthesize and share the core and scalable methods and lessons learned from the development and implementation of the digital system of the Patient Support Foundation to End TB. Results: The digital system was developed through multiple iterations, each of which includes gathering users’ feedback, building prototypes, testing the prototypes with users, developing, and piloting. Four key recommendations that should also be considered by other digital transformation projects in the health care sector include: (1) applying human-centered design (HCD) principles to clearly define the problems that the digital solutions aim to address in prior to and during technology development; (2) closely aligning the digital technologies with national strategies; (3) analyzing and adapting workflows to optimize the effectiveness of digital tools; and (4) applying global guidances and standards in digital technology development. Conclusions: Digital transformation in the health sector should prioritize an HCD approach throughout the design and implementation process. Early consideration and application of HCD principles are essential to developing digital solutions that are sustainable and usable.